Evaluation of the storage stability of four types of candied macapuno (Cocos nucifera Linn) - Oloroso, Maribeth G.; Alabastro, Estrella F. (1986.)
The storage stability of four types of candied macapuno was determined by following up the physical, chemical, and microbiological changes that took place in them at predetermined time interval. Sample AA contained no additive; sample BB had 2% propylene glycol (PG); sample CC had 2% PG and 10% glycerol; and sample DD contained 10% glycerol. The four types of samples in Run I were prepared separately and were packed in 0.003 cm LDPE bags. The samples in Run 2, however, were initially prepared as one batch (except for the final incorporation of the additives) and were packed in 0.007 cm LDPE bags whose WVTE value and permeability were determined to be 15.79 gm/m2-day and 0.5995 gm/m2 -day-mmHg (average of two trials), respectively. Samples in Run I were stored at 26.3-28.5°C and 93-98% RH while those for Run II were stored at 27.0-28.0°C and 92-95% RH. Sorption isotherms at 27-28°C for samples in Run II showed that among the substances added, it was glycerol, added singly, that effected the greatest shifting of the isotherm to the left of the control. Except for samples BB in Run I and CC in Run II, all samples either maintained or showed an increasing trend in their moisture content during storage. Fluctuations in a w values during storage were observed for most samples. The free fatty acid content, total plate count, and yeast and mold count, in general, demonstrated an increasing trend during storage. Results of sensory evaluation showed that rancid odor and flavor limited the acceptability of the sample without additive while attack of molds limited that of the other samples. PG alone was able to delay deterioration of samples due to mold growth by 10-13 days; glycerol alone delayed it by 7-11 days; and the combination of these two humectants was able to delay the deterioration by 17-20 days.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut; Macapuno, Candied